2015
DOI: 10.1038/srep09975
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Functional Plasticity of the Sensory-Motor Network in Patients with Cervical Spondylotic Myelopathy

Abstract: Several neuroimaging studies have suggested brain reorganisation in patients with cervical spondylotic myelopathy (CSM); however, the changes in spontaneous neuronal activity that are associated with connectedness remain largely unknown. In this study, functional connectivity strength (FCS), a data-driven degree centrality method based on a theoretical approach, was applied for the first time to investigate changes in the sensory-motor network (SMN) at the voxel level. Comparatively, CSM not only showed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 43 publications
10
48
0
1
Order By: Relevance
“…Previous anatomical studies have reported that neural plasticity occurs in the nervous system after spinal cord injury [36, 37]. Besides, intrinsic brain functional plasticity was also reported in CSM patients that the functional connectivity strength increased after CSM happened [38]. To our best knowledge, our study is the first demonstration of intrinsic functional plasticity on the spinal cord in CSM patients, and provides a possible explanation for neural development mechanism of CSM.…”
Section: Discussionsupporting
confidence: 71%
“…Previous anatomical studies have reported that neural plasticity occurs in the nervous system after spinal cord injury [36, 37]. Besides, intrinsic brain functional plasticity was also reported in CSM patients that the functional connectivity strength increased after CSM happened [38]. To our best knowledge, our study is the first demonstration of intrinsic functional plasticity on the spinal cord in CSM patients, and provides a possible explanation for neural development mechanism of CSM.…”
Section: Discussionsupporting
confidence: 71%
“…The multimodal integration regions were also vulnerable regions in MS according to previous studies[ 13 , 28 ]. Decreased activity levels in multimodal integration regions have been detected in a previous study on the “rubber hand illusion [ 13 , 29 ]” and also exist in cervical myelopathy patients with perception loss [ 30 ]. Our data also suggest that impaired connectivity in the multimodal integration regions was an important plastic adaptation due to MS pathology.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study, Zhou et al 42 studied functional connectivity strength (FCS) via resting-state functional connectivity (rsFC) MRI of the sensorimotor network. Patients with CSM showed significantly decreased FCS in the operculum-integrated regions, which exhibited reduced rsFC around the rolandic sulcus.…”
Section: Discussionmentioning
confidence: 99%